2013–2014 — a view from Greece. (8th December 2014) - Morgan, Catherine
Abstract : While much of the news reported from Greece continues to focus on the harsh realities of continuing financial crisis, it is a pleasure to publicize the strength and diversity of archaeological research, and the major developments which continue to make Greece's sites and museums ever more attractive and accessible to visitors whatever their interests. This has been an exciting year, not least thanks to the Greek presidency of the Council of the European Union which has put culture in all forms under the spotlight (the exhibition Greece's Europe. Colonies and Coinage from the Alpha Bank Collection at the Archaeological Museum of Thessaloniki was but one of the commemorative events held in Greece). Further new discoveries through the summer of 2014 continue to tantalize, as we will observe presently.